(3GdLhgQI GdNGdUI ef GdThGFH aj GdYbGFO GdfGbeI Ydi LejY GdePGgHs - (3TeS GdOjf YHO GdUeO Hf YHO Gddg GdYdhj GdOGeZGfj,J (B967 (3g` s ((3eMeO Hf CMeO Hf Ydi s)
(3ChdgG (B:s
(3GdMeO ddg Ydi LejY effg HGdcdjI hGdLRFjI MeOkG jcGaF fYeg hHYO aEfc CjgG GdCN GdeMH ai Gdgd YR hLd SCdJfi Yf ENJdGa GdCeI ai GdYbGFO s
(3BNQgG (B:s
(3hQMdJ dgG ai CcKQ GdCbWGQ , hNHQJ LejY ePGgH GdESdGe hWQGFagf Yf LejY eGge Ydjg , hGdSdGe JeJ s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3cJHJ GdahGJM HNW Sejcs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GNJdGa GdabgGAs